Association Between Serum Carcinoembryonic Antigen Levels at Different Perioperative Time Points and Colorectal Cancer Outcomes - Li, Zhenhui; Zhang, Dafu; Pang, Xiaolin; Yan, Shan; Lei, Ming; Cheng, Xianshuo; Song, Qian; Cai, Le; Wang, Zhuozhong; You, Dingyun (Frontiers in Oncology, 2021)
Background Whether elevated postoperative serum carcinoembryonic antigen (CEA) levels are prognostic in patients with stage II colorectal cancer (CRC) remains controversial. Patients and Methods Primary and sensitivity analysis populations were obtained from a retrospective, multicenter longitudinal cohort including consecutive patients without neoadjuvant treatment undergoing curative resection for stage I–III CRC. Serum CEA levels before (CEApre-m1) and within 1 (CEApost-m1), 2–3 (CEApost-m2–3), and 4–6 months (CEApost-m4–6) after surgery were obtained, and their associations with recurrence-free survival (RFS) and overall survival (OS) were assessed using Cox regression. Sensitivity and subgroup analyses were performed. Results Primary and sensitivity analysis populations included 710 [415 men; age, 54.8 (11.6) years] and 1556 patients [941 men; age, 56.2 (11.8) years], respectively. Recurrence hazard ratios (HRs) in the elevated CEApre-m1, CEApost-m1, CEApost-m2–3, and CEApost-m4–6 groups were 1.30 (95% CI: 0.91–1.85), 1.53 (95% CI: 0.89–2.62), 1.88 (95% CI: 1.08–3.28), and 1.15 (95% CI: 0.91–1.85), respectively. The HRs of the elevated CEApre-m1, CEApost-m1, CEApost-m2–3, and CEApost-m4–6 groups for OS were 1.09 (95% CI: 0.60–1.97), 2.78 (95% CI: 1.34–5.79), 2.81 (95% CI: 1.25–6.30), and 3.30 (95% CI: 1.67–.536), respectively. Adjusted multivariate analyses showed that both in the primary and sensitivity analysis populations, elevated CEApost-m2–3, rather than CEApre-m1, CEApost-m1, and CEApost-m4–6, was an independent risk factor for recurrence, but not for OS. The RFS in the elevated and normal CEApost-m2–3 groups differed significantly among patients with stage II disease [n = 266; HR, 2.89; 95% CI, 1.02–8.24 (primary analysis); n = 612; HR, 2.69; 95% CI, 1.34–5.38 (sensitivity analysis)]. Conclusions Elevated postoperative CEA levels are prognostic in patients with stage II CRC, with 2–3 months after surgery being the optimal timing for CEA measurement.